Eating Habits of Adolescent Students - Omera Naseer , Fazal Mahmood , Masood Fazil ,Sana Bilal , Afifa Kulsoom , Sidra Hamid , Omera Naseer , Fazal Mahmood , Masood Fazil ,Sana Bilal , Afifa Kulsoom , Sidra Hamid (Journal of Rawalpindi Medical College, 2018)
Background: To assess eating habits of adolescent students of Rawalpindi. Methods: In this descriptive study 276 students of both genders, aged between 13-16 yrs were selected through two stage cluster sampling technique. Data was collected by means of structured questionnaire. Questionnaire asked information regarding demographics and eating habits i.e. the type of the food group being consumed and the frequency of consumption of these foods, based on United States Department of Agriculture (USDA) food guide pyramid. Results: Majority( 75.7%) had unhealthy eating habits, while 19.9 had satisfactory and only 4.4% had healthy eating habits. Majority of the students(40.6%) ate fruits and vegetables 2-3 times a week, while 32.6% never drank milk and 13% never ate meat. Conclusion: Majority of the adolescent students had unhealthy eating habits and did not take the food groups as recommended by United States Department of Agriculture (USDA) food guide pyramid (FGP).